EFFECT OF SURYANAMASKAR WITH KRIYA PRACTICES ON SELECTEDMOTOR FITNESS COMPONENTS AMONG INTER COLLEGIATE CRICKET MEN PLAYERS - PHANEENDRA, Dr.V.V.M.U. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The purpose of the study was to Effect of Suryanamaskar with Kriya Practices on Selected Motor Fitness Components among Inter Collegiate Cricket men players, a total of 20 students’ from Adikavi Nannaya University, Rajamahendravaram, Andhra Pradesh, India Were selected as subjects and their Age ranged between 20-23 years. They were divided into experimental and control group randomly, after the pre-and post test the subject (N-20) was randomly assigned into two equal groups of 10 athletes each. The group were assigned as experimental group and control group. The experimental group underwent suryanamaskar with kriya practice for a period of eight weeks. The post tests were conducted on the above said variables. The training programme was schedule as 6.00 am-7.00am for three alternative days in a week, The data collected from the two group namely suryanamaskar with kriya practices group and control group on selected motor components were statistically analyzed by using T ratio in order to determinate the difference if any among the group at pre-post test. The calculated T ratio is tested for significant at 0.05 level of confident, Suryanamaskar with kriya practice had significantly developed the speed, agility, flexibility, balance of the inter collegiate men Cricket players.